Miscellaneous Marine Toxins of Medical Significance - Haddad, Vidal [UNESP]; Haddad, V; Tubaro, A.; Kim, E.; Kem, W. R.; Gopalakrishnakone, P. (Springer, 2016)
Subaquatic life is in a state of constant mechanical and chemical warfare in which the best adapted will survive. In these complex interactions, some animals can present structures that will inflict trauma, such as teeth, spines, and stings, which can be venomous or not. Studies on toxins of dinoflagellates and cyanobacteria are expanding, and disease outbreaks associated with these toxins are increasing globally. These poisonings can occur in an individual (as the paralysis for seafood) and in small or large groups (such as the red tides). Various marine animals used as food may be contaminated, which broadens the spectrum of these poisonings and increases the need for additional studies on the activity of these toxins and their mechanisms of action. Studies on therapeutic measures and approaches to reduce or eliminate the risk in the environment are also needed. Injuries caused by sea urchins are common around the world. Some species cause severe envenomations, but the majority of these injuries are traumatic and not serious. Sea cucumbers can be toxic, and the crown-of-thorns starfish is venomous. Additionally, sea worms present toxins and bristles that cause skin inflammation and are also responsible for painful bites. They are common on the coasts, and the clinical manifestations caused by marine worms present similarity with injuries caused by marine sponges. Leeches do not cause envenomations and rarely are associated with marked manifestation in humans.